Mecanismos linguísticos e relações intersubjetivas na produção de textos : atividades enunciativas na prática de ensino - Barros, Solange Christiane Gonzalez (2017)
In this study called Linguistic mechanisms and intersubjective relations in textual production: enunciative activities in the teaching practice, the aim is to recall questions from the Master’s degree, such as the difficulty that students have to insert notions of qualification as explicit marks of intersubjective regulation (commented world) in their textual productions. Analysing, now, a practical work to be done in school contexts and considering the difficulties observed in the students’ textual production, we have the objective to i. explore more deeply the process of constitution of enunciative plans which involve linguistic mechanisms as marks of intersubjective regulation, especially the appreciative modality, which marks the enunciator’s point of view – favourable or unfavourable – about a content that is constructed linguistically; ii. determine and analyse the use of the appreciative modality in a corpus constituted of narrative texts, especially fables; iii. propose linguistic practices to be applied in the exercise of textual production aiming to explore, in the language teaching, the language process which can promote the students’ linguistic-cognitive development. It is used in this work the Theory of Predicative and Enunciative Operations proposed by the French linguist Antoine Culioli.